Effect of regeneration on the thermo-ecological performance analysis and optimization of irreversible air refrigerators - Ust, Yasin (SPRINGER, 2010)
A thermo-ecological performance analysis of an irreversible regenerative air refrigerator cycle exchanging heat with thermal reservoirs is presented. In the analysis, the external irreversibility effects due to heat transfer across finite temperature differences and the heat leak loss between the external heat reservoirs while the internal irreversibilities are due to the non-isentropic compression and expansion processes and the regenerative loss are taken into account. The effects of regeneration and heat sources temperature ratio are given special emphasis and investigated in detail. A comparative performance analysis considering the objective functions of an ecological coefficient of performance, exergetic efficiency and coefficient of performance is also carried out. The maximum of the objective functions and the corresponding optimal conditions have been derived analytically. The obtained results may provide a general theoretical tool for the thermo-ecological design of regenerative air refrigerators.
Keywords: ENTROPY GENERATION MINIMIZATION; LOAD DENSITY OPTIMIZATION; COOLING-LOAD; THERMODYNAMICS; COEFFICIENT; CRITERION; CYCLES; Mechanics